Integrated pest management strategies for a terrestrial isopod, Armadillidium vulgare, in no-till soybean production - Alfaress, Serine (Kansas State University, 2012)
No-till management of soybean benefits producers by lowering input costs and retaining soil moisture, but may also provide optimal conditions for increasing populations of soil-inhabiting pests. For Kansas soybean, damaging populations of soil-inhabiting isopods (Malacostraca: Isopoda) have been observed in fields under no-tillage management. To control damage to soybean stands from feeding isopods, current management strategies need to be evaluated. The objectives of my research were to evaluate the effects of chemical and cultural control combinations (seed treatment and planting date, planting date and seed size, seed treatment and natural crop residue removal, and seeding rate and seed treatment) on soybean stand densities exposed to natural isopod populations, and to evaluate the effects of burning crop residue on isopod populations and emergence rates in soybean under no-tillage management. Field studies were conducted in consecutive years (2009 and 2010) in two separate soybean fields within each year. All fields were under no-till management and had a history of damaging isopod populations. In the second chapter, we demonstrated that seed treatment with an insecticide is not a reliable strategy. Doubling normal seeding rates can potentially reduce the number of trips a grower makes across a field (single, high-density versus multiple, low-density plantings). In doing so, growers may save time and money (e.g., fuel). A high seeding rate (563,380/ha), along with a low rate (50 g a.i. / 100 kg seed) of neonicotinoid seed treatment, appears to improve soybean stands (P < 0.05). No other combinations of control methods appeared to affect stand density. In the third chapter, we show burning to be an effective strategy to directly influence isopod populations but its overall effect on soybean stands needs further investigation.
Keywords: Pest management; Terrestrial isopod; Armadillidium vulgare; No till; Soybean production; Burning crop residue; Agriculture, General (0473); Entomology (0353)